Promoting integrated passenger transport solutions using a business approach. Issue 1 (March 2015) - Reis, Vasco; Macário, Rosário
Highlights: Call for the provision of seamless passenger transport services across the EU. Low interest by transport operators as risks of integration often offset the benefits. Transport Operators may be willing to integrate provided a business rationale. Prototypes of business models ready to support the implementation of intermodality. Abstract: In the 2011 White Paper on Transport, the European Commission calls for the provision of seamless passenger transport services across the European Union. The vision entails the integration of two transport systems that are quite independent of each other: the urban and interurban systems. Expectations of extensive integration amongst transport operators may, however, be unrealistic, since the risks (e.g.: the sharing of sensitive information) often offset the eventual benefits (e.g.: increased ridership). Indeed, the main beneficiaries of integration include the passengers (e.g.: through reduced travel times) and the society (e.g.: through a reduction in energy consumption), which is, in itself, justification enough for public intervention. However, recent economic turmoil has placed significant pressure on national budgets and exhausted most of the capacity for deploying financial incentives, making it necessary to come up with alternatives. In this paper we argue that transport operators could willingly integrate, as long as a business rationale is provided. Accordingly, achieving the European Commission's ambition depends on the ability to identify successful business models for integrated transport services. A business model describes a company's way of doing business and generating profits, by specifying its positioning in the value chain. The results of the investigation show the existence of a business rationale in the integration of transport services that could be exploited through implementation of an adequate business model. Based on the results of eleven case studies, we designed two business model prototypes. Each prototype is meant to overcome specific contextual barriers to integration: located at the transport links and at the nodes.